Assessment of the impact of community library services: a case study of Khomas region, Namibia - Haindaka, Shihawa Alberthina (Department of Knowledge and Information Stewardship, 2025)
Community libraries play a crucial role in addressing the inequality stemming from the apartheid era through the provision of a cohesive system aimed at offering free access to library services to equip users with necessary knowledge and skills for lifelong learning and support education. However, community libraries are under scrutiny to demonstrate their value to secure funding and the lack of literature regarding the impact of community library services is perhaps the reason why community libraries are under increasing pressure to capture and demonstrate their value to society and stakeholders. The lack of literature on the holistic impact of community library services is one of the factors contributing to the library budget cuts. Hence, the broad objective of this study was to assess the impact of community library services in Khomas region, Namibia. The study was informed by Service Quality Models to explore the economic, social and cultural benefits of community library services, so as to provide a more holistic understanding of the impact of community libraries. A mixed methods research approach and a multiple case study design were employed to address the study objective. The study collected data through printed questionnaires with 381 random sampled library users and face-to-face semi-structured interviews with 10 purposively sampled librarians from the six selected community libraries across Khomas region. The study found that library services such as free internet access services; basic ICT training services and after school programs were beneficial to library users. The free provision of services in community libraries positively influences users' skill development, academic performances, personal success, knowledge gain, social inclusion and cultural advancements. The lack of reliable ICT facilities emerged as a major challenge which is a result of the lack of intentional funding for acquisition and maintenance of ICT facilities, a key aspect to lessening the digital divide. Moreover, management issues between City of Windhoek and Ministry of Education in managing community libraries was also noted as a key challenge. While community libraries are beneficial to library users, there was no system in place to holistically capture community libraries' impact beyond statistics. The study's suggests that community libraries need to prioritize funding for ICT infrastructure, explore new librarian roles to support library marketing efforts and develop systems to capture tangible evidence of library services impact, beyond statistical accumulation of library service usage.